Targeting Oncoproteins for Degradation by Small Molecule-Based Proteolysis-Targeting Chimeras (PROTACs) in Sex Hormone-Dependent Cancers - Liu, Li; Shi, Lihong; Wang, Zhaodi; Zeng, Jun; Wang, Yue; Xiao, Hongtao; Zhu, Yongxia (Frontiers in Endocrinology, 2022)
Sex hormone-dependent cancers, including breast, ovary, and prostate cancer, contribute to the high number of cancer-related deaths worldwide. Steroid hormones promote tumor occurrence, development, and metastasis by acting on receptors, such as estrogen receptors (ERs), androgen receptors (ARs), and estrogen-related receptors (ERRs). Therefore, endocrine therapy targeting ERs, ARs, and ERRs represents the potential and pivotal therapeutic strategy in sex hormone-dependent cancers. Proteolysis-targeting chimeras (PROTACs) are a novel strategy that can harness the potential of the endogenous ubiquitin-proteasome system (UPS) to target and degrade specific proteins, rather than simply inhibiting the activity of target proteins. Small molecule PROTACs degrade a variety of proteins in cells, mice, and humans and are an emerging approach for novel drug development. PROTACs targeting ARs, ERs, ERRs, and other proteins in sex hormone-dependent cancers have been reported and may overcome the problem of resistance to existing endocrine therapy and receptor antagonist treatments. This review briefly introduces the PROTAC strategy and summarizes the progress on the development of small molecule PROTACs targeting oncoproteins in sex hormone-dependent cancers, focusing on breast and prostate cancers.